Indigenous Technical Knowledge and Its Potential Application to Uganda's Pig Sub‐Sector - Junior Senyonga Kasima; Basil Mugonola; Harriet Muyinza; Sarah Kizza‐Nkambwe; Geoffrey Akiiki Beyihayo; Kenneth Kidega; James Nokrach; Maxmillan Mpewo; Marx Kisaame; Elly Kurobuza Ndyomugyenyi (Modern Agriculture)
ABSTRACT Uganda's pork consumption is speculated to exceed any other livestock meat consumption by 2050. However, the current trend in pig production may not meet the demand due to pig production constraints such as recurrent disease incidences and high feeding costs. The proposed modern practices are not cost‐effective, especially for resource‐constrained pig farmers. This review, therefore, synthesises previous studies on the practicability of integrating Indigenous Technical Knowledge (ITK) in pig production to mitigate the prevailing pig production challenges in Uganda. By employing ITK, smallholder farmers have realised that indigenous pig breeds are disease‐resistant and suit the prevailing harsh tropical conditions. In addition, affordable plant‐based concoctions have been developed to cure diseases in pigs. For example, Centella asiatica has been identified as a potential purgative for diarrhoeal infections. Integrating pigs in cropping systems has also been adopted as a low‐cost alternative to effectively feed pigs for optimal performance. Fortunately, most of the ITK options for solving pig production challenges are feasible in Uganda. Thus, ITK should be embedded in the country's extension system to increase smallholder farmers' awareness about its potential of improving pig production. An ITK‐modern technology integration would probably meet the acceptance and be suitable for commercial pig producers.